Transition metal composite material and preparation method and application thereof

By using foam transition metal composite materials as catalysts, the problem of slow OER reaction kinetics in traditional electrolytic hydrogen production process is solved, and the cycle stability of the battery is improved in sodium ion batteries.

CN119592989AInactive Publication Date: 2025-03-11PINGYU ZHONGXING ENERGY CO LTD

Patent Information

Application Number
CN202510142446.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the traditional process of electrolyzing hydrogen production, the oxygen evolution reaction (OER) kinetics of the anode are slow, and the precious metal catalysts are costly and have low reserves, which limits their large-scale commercial applications.

Method used

A transition metal composite material is used, which includes a conductive substrate, an adsorption layer and a catalytic activity enhancement layer. The conductive matrix is ​​a foam transition metal, the adsorption layer is a transition metal oxide, and the catalytic activity enhancement layer is a layered bimetal hydroxide. The composite material is prepared by electrochemical oxidation and hydrothermal reactions to enhance the kinetics and durability of the OER reaction.

Benefits of technology

It improves the kinetics and durability of the OER reaction, reduces the use of transition metals, and acts as an acidic substance adsorbent in sodium ion batteries, improving the capacity retention rate and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592989A_ABST
    Figure CN119592989A_ABST
Patent Text Reader

Abstract

The invention provides a transition metal composite material, a preparation method and application thereof and a sodium ion battery, and belongs to the technical field of electrochemistry. The transition metal composite material comprises a conductive substrate, an adsorption layer coating the surface of the conductive substrate and a catalytic activity enhancement layer coating the surface of the adsorption layer, the conductive substrate is made of foam transition metal; the adsorption layer is composed of oxide of transition metal in the conductive substrate; and the catalytic activity enhancement layer is composed of layered double hydroxides. The transition metal composite material is good in structural stability, OER activity and durability, the adsorption and conversion process of an OER reaction intermediate can be effectively promoted, and therefore improvement of OER reaction kinetics is promoted; and the transition metal composite material can effectively absorb acidic materials such as HF, CO2 and the like generated in the cycle process of the sodium-ion battery, so that the capacity retention ratio and the cycle stability of the sodium-ion battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrochemical technology, and specifically relates to a transition metal composite material and a preparation method and application thereof, and a sodium ion battery. Background Art

[0002] Hydrogen is a clean fuel with high energy density, conversion efficiency and zero carbon emission. There are many ways to produce hydrogen, such as methane reforming, water gas method, water electrolysis method, etc. Among them, water electrolysis has the characteristics of high product purity and high efficiency, and has gradually become a promising way to produce hydrogen.

[0003] However, in the traditional process of hydrogen production by electrolysis of water, the oxygen evolution reaction (OER) at the anode has slow reaction kinetics, which reduces the efficiency of water electrolysis. At present, the commonly used catalysts for OER are precious metal catalysts with heavy metals such as Ir, Ru, and Pt as the main components. Precious metal catalysts can produce active sites with optimal OER intermediate binding energy, effectively reduce the energy barrier of OER, and improve the efficiency of OER reaction. However, the reserves of these precious metals are low and the prices are high, which limits their large-scale commercial application. Based on this, technicians in this field began to look for other OER catalysts.

[0004] Transition metals are abundant in reserves and relatively inexpensive. Studies have shown that transition metal OER catalysts prepared based on transition metal alloys, oxides, oxyhydroxides, nitrogen, phosphides, etc. have excellent OER catalytic performance that is not inferior to currently commercialized precious metal catalysts (such as RuO2 and IrO2). However, the transition metal OER catalysts currently on the market still have the problem of insufficient durability. Summary of the invention

[0005] The object of the present invention is to provide a transition metal composite material, a preparation method and application thereof, and a sodium ion battery. The transition metal composite material provided by the present invention has good structural stability, can effectively promote the adsorption and conversion process of OER reaction intermediates, thereby promoting the improvement of OER reaction kinetics, and has good OER activity and durability. Moreover, the transition metal composite material provided by the present invention can also be added to the sodium ion battery as an acidic substance adsorbent, effectively absorbing HF, CO2 and other acidic substances generated by the electrolyte during the circulation process of the sodium ion battery, and effectively preventing the acidic substances from reacting with the positive and negative electrode materials and the electrolyte inside the sodium ion battery, thereby effectively improving the capacity retention rate and cycle stability of the sodium ion battery.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a transition metal composite material, comprising a conductive substrate, an adsorption layer coated on the surface of the conductive substrate, and a catalytic activity enhancement layer coated on the surface of the adsorption layer; The conductive substrate is a foam transition metal; the foam transition metal includes foam iron, foam cobalt, foam copper, foam nickel, foam zinc, foam manganese or foam titanium; The adsorption layer is composed of oxides of transition metals in the conductive substrate; The catalytic activity enhancement layer is composed of layered double metal hydroxides with a molecular formula of M1M2-LDH, where M1 includes Co, Cu, Ni, Zn, Mn or Ti, and M2 is Fe.

[0007] Preferably, the foamed transition metal is a three-dimensional network structure; and the thickness of the conductive substrate is 0.3-2 mm.

[0008] Preferably, the transition metal composite material comprises a plurality of lamellar structure particles; each of the lamellar structure particles has a diameter of 10-30 nm and a thickness of 500-1000 nm.

[0009] The present invention provides a method for preparing the transition metal composite material described in the above technical solution, comprising the following steps: Electrochemically oxidizing the surface of a transition metal foam to obtain a precursor; the precursor comprises a conductive substrate and an adsorption layer coated on the surface of the conductive substrate; the conductive substrate is a transition metal foam, and the transition metal foam comprises iron foam, cobalt foam, copper foam, nickel foam, zinc foam, manganese foam or titanium foam, and the adsorption layer is composed of oxides of the transition metal in the conductive substrate; The precursor is placed in a precursor liquid for hydrothermal reaction to form a catalytic activity enhancement layer on the surface of the precursor to obtain the transition metal composite material; the precursor liquid is an alkaline aqueous solution containing transition metal ions; the transition metal ions include first transition metal ions and second transition metal ions; the first transition metal ions include Co ions, Cu ions, Ni ions, Zn ions, Mn ions or Ti ions; the second transition metal ions are Fe ions; the composition of the catalytic activity enhancement layer is a layered double metal hydroxide with a molecular formula of M1M2-LDH, where M1 includes Co, Cu, Ni, Zn, Mn or Ti, and M2 is Fe.

[0010] Preferably, the electrochemical oxidation is carried out in an electrolyte; the conditions of the electrochemical oxidation include: an oxidation time of 50 to 200 s and a load voltage of 1.2 to 2.5 V.

[0011] Preferably, the electrolyte comprises a KOH aqueous solution, and the concentration of the KOH aqueous solution is 0.2-2 mol / L.

[0012] Preferably, the precursor solution comprises a first transition metal salt, a second transition metal salt, ammonium fluoride, urea and water; the first transition metal salt comprises Co salt, Cu salt, Ni salt, Zn salt, Mn salt or Ti salt, and the second transition metal salt is Fe salt; the concentration of the first transition metal ion in the precursor solution is 0.004~0.05mmol / L, and the concentration of the second transition metal ion is 0.004~0.05mmol / L; the temperature of the hydrothermal reaction is 110~165℃, and the insulation time is 6~18h.

[0013] The present invention provides the transition metal composite material described in the above technical solution or the use of the transition metal composite material described in the above technical solution as an OER catalyst or in a sodium ion battery.

[0014] The present invention provides a sodium ion battery, comprising a positive electrode, a negative electrode, an electrolyte and an acidic substance absorbing diaphragm; the acidic substance absorbing diaphragm comprises a polypropylene base film and an acidic substance adsorption slurry layer coated on the surface of the polypropylene base film; the coating method comprises an extrusion coating method, a gravure coating method or a dip coating method; the raw material for preparing the acidic substance adsorption slurry layer comprises the transition metal composite material described in the above technical solution or the transition metal composite material described in the above technical solution.

[0015] Preferably, the mass proportion of the transition metal composite material in the acidic substance absorption membrane is 5% to 15%; the electrolyte is a liquid containing sodium hexafluorophosphate; the constituent material of the positive electrode includes composite sodium iron phosphate; and the constituent material of the negative electrode includes hard carbon.

[0016] The present invention provides a transition metal composite material, comprising a conductive substrate and an adsorption layer coated on the surface of the conductive substrate and a catalytic activity enhancing layer coated on the surface of the adsorption layer; the conductive substrate is a foam transition metal; the foam transition metal includes foam iron, foam cobalt, foam copper, foam nickel, foam zinc, foam manganese or foam titanium; the adsorption layer is composed of the oxide of the transition metal in the conductive substrate; the catalytic activity enhancing layer is composed of a layered double metal hydroxide with a molecular formula of M1M2-LDH, where M1 includes Co, Cu, Ni, Zn, Mn or Ti, and M2 is Fe. The foam transition metal in the conductive substrate of the present invention has good electrical conductivity and can promote the rapid conduction of electrons during the OER reaction. At the same time, the oxide of the transition metal in the adsorption layer can form hydroxyl oxides during the OER reaction to improve the OER reaction kinetics; taking a transition metal composite material with a molecular formula of CoFe-LDH formed by using foam iron as a conductive substrate as an example, the component in the adsorption layer is Fe2O3, and Fe2O3 can form FeOOH during the OER reaction, and can further form Co with Co 2+ -O-Fe 3+ , which can effectively reduce the energy barrier of the OER reaction and improve the OER reaction kinetics. Moreover, the oxide of the transition metal in the adsorption layer can effectively adsorb the adsorption and transfer process of the OER reaction intermediates (*O, *OH, *OOH), thereby improving the OER catalytic activity of the transition metal composite material. In addition, the outermost catalytic activity enhancement layer can continuously reconstruct the surface electronic structure during long-term operation, continuously exposing new catalyst active sites, thereby improving the OER durability of the transition metal composite material. Therefore, the transition metal composite material of the present invention has good structural stability, OER activity and durability.

[0017] Furthermore, in the present invention, the foamed transition metal has high hardness and can realize self-support of the transition metal composite material; at the same time, the foamed transition metal has a layered porous microstructure and a high specific surface area, which provides abundant active sites for M1M2-LDH layered double metal hydroxide (M1 includes Co, Cu, Ni, Zn, Mn or Ti, M2 is Fe) and transition metal oxides, which is beneficial to increase their loading capacity, and can also reduce the agglomeration of the obtained transition metal composite material and improve its dispersibility; at the same time, it can improve the electron transmission capacity during the OER reaction and enhance the conductivity of the transition metal composite material. Moreover, there is a synergistic effect between the M1M2-LDH layered double hydroxide and the transition metal oxide. On the one hand, the M1M2-LDH layered double hydroxide can produce transition metal oxides alone to improve the OER catalytic activity of the resulting transition metal composite material. On the other hand, the transition metal oxide can also supplement the transition metal elements consumed / shed during the OER reaction for the M1M2-LDH layered double hydroxide, thereby improving the durability of the transition metal composite material. Moreover, this synergistic effect can optimize the electronic structure and local environment on the surface of the transition metal composite material, effectively promote the adsorption and conversion process of the OER reaction intermediates (M-*OH→M-*O→M-*OOH→O2, M is a transition metal), thereby promoting the improvement of the OER reaction kinetics. Furthermore, the transition metal composite material of the present invention has a three-dimensional layered structure, has a rich electrochemically active surface area, can expose a rich active site, and promotes the transmission of reaction intermediates and gases.

[0018] The present invention provides a method for preparing the transition metal composite material. The present invention combines different functional layers to obtain the transition metal composite material, wherein the preparation processes of the functional layers are independent of each other and do not interfere with each other. The self-supporting transition metal composite material formed by this step-by-step functionalization method has larger voids, which increases the specific surface area; when the transition metal composite material is used as an OER catalyst in OER, the pores can provide an entry path for the electrolyte, ensuring the formation of a three-phase interface of the OER catalyst, reactants and electrolyte; at the same time, the surface active sites of the OER catalyst are increased, the functionalized structure of the OER catalyst is optimized, the utilization rate of the catalyst active sites is increased, and the amount of transition metal used is reduced.

[0019] Furthermore, in the traditional preparation process of transition metal-based catalysts for OER, the metal salt corresponding to the transition metal is generally dissolved in water, and the catalyst powder is obtained through hydrothermal, drying, and grinding processes. The catalyst powder and the binder are mixed into a slurry, coated on the working electrode (generally a glassy carbon sheet), and then dried, so that the transition metal-based catalyst can play a role. In the present invention, a layered double hydroxide is grown in situ on a composite substrate comprising a foamed transition metal and an oxide of the transition metal in the foamed transition metal to obtain a transition metal composite material; when the transition metal composite material is used as an OER catalyst, the transition metal composite material can be fixed to the electrode without adding an additional binder, and the layered double hydroxide grown in situ is more stable than that adhered with a binder, and is not easy to fall off during the reaction. That is, the transition metal composite material obtained according to the preparation method provided by the present invention has excellent structural stability.

[0020] In addition, the preparation process of the transition metal composite material of the present invention is carbon-free and adhesive-free, which can avoid the problem of catalytic layer shedding caused by adhesive aging and carbon corrosion. The preparation process is simple and the preparation cost is low.

[0021] The present invention provides a sodium ion battery, comprising a positive electrode, a negative electrode, an electrolyte and an acidic substance absorbing diaphragm; the acidic substance absorbing diaphragm comprises a polypropylene base film and an acidic substance adsorption slurry layer coated on the surface of the polypropylene base film; the coating method comprises an extrusion coating method, a gravure coating method or a dip coating method; the raw material for preparing the acidic substance adsorption slurry layer comprises the transition metal composite material described in the above technical solution or the transition metal composite material described in the above technical solution. The transition metal composite material provided by the present invention can effectively absorb acidic substances such as HF and CO2 generated by the electrolyte, and effectively prevent the acidic substances from having side reactions with the positive and negative electrode materials and the electrolyte inside the sodium ion battery, thereby effectively improving the capacity retention rate and cycle stability of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0023] Figure 1 This is the XRD characterization diagram of the CoFe-LDH / Fe2O3 / Fe composite material obtained in Example 1; Figure 2 This is a SEM image of the CoFe-LDH / Fe2O3 / Fe composite material obtained in Example 1; Figure 3 It is a comparison diagram of the overpotential of the transition metal composite material obtained in Examples 1 to 3, the RuO2 / Fe2O3 / Fe composite material obtained in Comparative Example 1, and the foam transition metal sample obtained in Comparative Example 2; Figure 4 Electrochemical impedance spectroscopy of the transition metal composite materials obtained in Examples 1 to 3, the RuO2 / Fe2O3 / Fe composite material obtained in Comparative Example 1, and the foamed transition metal sample obtained in Comparative Example 2; Figure 5 It curves of the transition metal composite materials obtained in Examples 1 to 3, the RuO2 / Fe2O3 / Fe composite materials obtained in Comparative Example 1, and the foamed transition metal sample obtained in Comparative Example 2. DETAILED DESCRIPTION

[0024] The present invention provides a transition metal composite material, comprising a conductive substrate, an adsorption layer coated on the surface of the conductive substrate, and a catalytic activity enhancement layer coated on the surface of the adsorption layer; The conductive substrate is a foam transition metal; the foam transition metal includes foam iron, foam cobalt, foam copper, foam nickel, foam zinc, foam manganese or foam titanium; The adsorption layer is composed of oxides of transition metals in the conductive substrate; The catalytic activity enhancement layer is composed of layered double metal hydroxides with a molecular formula of M1M2-LDH, where M1 includes Co, Cu, Ni, Zn, Mn or Ti, and M2 is Fe.

[0025] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art or are prepared by methods well known to those skilled in the art.

[0026] The transition metal composite material of the present invention includes a conductive matrix, and the thickness of the conductive matrix can be 0.3~2mm; in a specific embodiment of the present invention, the thickness of the conductive matrix is ​​1mm. In the present invention, the conductive matrix is ​​a foam transition metal, and the foam transition metal can be a three-dimensional network structure. The foam transition metal of the present invention includes foam iron, foam cobalt, foam copper, foam nickel, foam zinc, foam manganese or foam titanium; in a specific embodiment of the present invention, the foam transition metal is foam iron, and the porosity of the foam iron is 98% and the specific surface area is 30cm² / cm³. In the present invention, the foam transition metal can supplement the transition metal ions for the adsorption layer and the catalytic activity enhancement layer to make up for the transition metal loss during the reaction. At the same time, the foam transition metal has good electrical conductivity and can ensure the rapid conduction of electrons during the OER reaction. Moreover, the foam transition metal has high hardness and can realize the self-support of the transition metal composite material. At the same time, the foamed transition metal has a layered and porous microstructure and a high specific surface area, which provides abundant active sites for the components of the adsorption layer and the catalytic activity enhancement layer, thereby increasing their loading capacity, reducing the agglomeration of the resulting transition metal composite material, and improving its dispersion; at the same time, it can enhance the electron transmission capacity during the OER reaction and enhance the conductivity of the resulting transition metal composite material.

[0027] The transition metal composite material of the present invention includes an adsorption layer. In the present invention, the composition of the adsorption layer is the oxide of the transition metal in the conductive matrix. In the present invention, the foamed transition metal in the conductive matrix has good conductivity and can promote the rapid conduction of electrons during the OER reaction. At the same time, the oxide of the transition metal in the adsorption layer can form hydroxyl oxides during the OER reaction, thereby improving the OER reaction kinetics. Taking a transition metal composite material with a molecular formula of CoFe-LDH formed by using foamed iron as a conductive matrix as an example, the component in the adsorption layer is Fe2O3, and Fe2O3 can form FeOOH during the OER reaction, and can further form Co 2+ -O-Fe 3+ , which can effectively reduce the energy barrier of the OER reaction and improve the OER reaction kinetics. Furthermore, the oxides of transition metals in the adsorption layer can effectively adsorb the adsorption and transfer process of OER reaction intermediates (*O, *OH, *OOH), promoting the OER catalytic activity of transition metal composite materials.

[0028] The transition metal composite material of the present invention includes a catalytic activity enhancement layer. In the present invention, the composition of the catalytic activity enhancement layer is a layered double metal hydroxide with a molecular formula of M1M2-LDH, where M1 includes Co, Cu, Ni, Zn, Mn or Ti, and M2 is Fe; in a specific embodiment of the present invention, the molecular formula of the catalytic activity enhancement layer can be CoFe-LDH, NiFe-LDH, ZnFe-LDH, MnFe-LDH or CuFe-LDH. In the present invention, the catalytic activity enhancement layer can continuously reconstruct the surface electronic structure during long-term operation, continuously exposing new catalyst active sites, thereby improving the OER durability of the transition metal composite material. Moreover, there is a synergistic effect between the M1M2-LDH layered double hydroxide and the transition metal oxides. On the one hand, the M1M2-LDH layered double hydroxide can produce oxides of a single transition metal to enhance the OER catalytic activity of the resulting transition metal composite material. On the other hand, the transition metal oxides can also replenish the transition metal elements consumed / shed during the OER reaction for the M1M2-LDH layered double hydroxide, thereby enhancing the durability of the catalyst. This synergistic effect can optimize the electronic structure and local environment on the surface of the transition metal composite material, effectively promoting the adsorption and conversion process of the OER reaction intermediates (M-*OH→M-*O→M-*OOH→O2, where M is a transition metal), thereby promoting the improvement of the OER reaction kinetics.

[0029] The transition metal composite material of the present invention has a three-dimensional layered structure and a rich electrochemically active surface area, which can expose a rich number of active sites and promote the transmission of reaction intermediates and gases.

[0030] The present invention also provides a method for preparing the transition metal composite material described in the above technical solution, comprising the following steps: Electrochemically oxidizing the surface of a transition metal foam to obtain a precursor; the precursor comprises a conductive substrate and an adsorption layer coated on the surface of the conductive substrate; the conductive substrate is a transition metal foam, and the transition metal foam comprises iron foam, cobalt foam, copper foam, nickel foam, zinc foam, manganese foam or titanium foam, and the adsorption layer is composed of oxides of the transition metal in the conductive substrate; The precursor is placed in a precursor liquid for hydrothermal reaction to form a catalytic activity enhancement layer on the surface of the precursor to obtain the transition metal composite material; the precursor liquid is an alkaline aqueous solution containing transition metal ions; the transition metal ions include first transition metal ions and second transition metal ions; the first transition metal ions include Co ions, Cu ions, Ni ions, Zn ions, Mn ions or Ti ions; the second transition metal ions are Fe ions; the composition of the catalytic activity enhancement layer is a layered double metal hydroxide with a molecular formula of M1M2-LDH, where M1 includes Co, Cu, Ni, Zn, Mn or Ti, and M2 is Fe.

[0031] In the present invention, the foamed transition metal can be subjected to ultrasonic treatment, washing and drying in sequence before use. The ultrasonic treatment in the present invention can be a first ultrasonic treatment and a second ultrasonic treatment carried out in sequence. In the present invention, the first ultrasonic treatment can be carried out in dilute hydrochloric acid; the mass fraction of the dilute hydrochloric acid can be 2-10%; the frequency of the first ultrasonic treatment can be 50-70kHz, and the time can be 5-20min. In the present invention, the second ultrasonic treatment can be carried out in acetone; the frequency of the second ultrasonic treatment is 50kHz, 60kHz or 70kHz; the time can be 5-20min. In a specific embodiment of the present invention, the first ultrasonic treatment is carried out in dilute hydrochloric acid with a mass fraction of 3%, the frequency of the first ultrasonic treatment is 50kHz, 60kHz or 70kHz, and the time is 15min; the frequency of the second ultrasonic treatment is 50kHz, 60kHz or 70kHz, and the time is 15min. The present invention removes oil and impurities on the surface of the foamed transition metal by ultrasonic treatment. The washing in the present invention includes alcohol washing and water washing carried out in sequence; the reagent used for the alcohol washing can be anhydrous ethanol. The drying in the present invention can be carried out in N2 atmosphere.

[0032] The present invention oxidizes the surface of the foam transition metal to obtain a precursor. In the present invention, the electrochemical oxidation can be carried out in an electrolyte. In a specific embodiment of the present invention, the foam transition metal is placed in an electrolyte and the foam transition metal is electrochemically oxidized to obtain a precursor. The electrochemical oxidation of the present invention can be carried out in an oxygen atmosphere. In the present invention, the electrolyte can include a KOH aqueous solution, and the concentration of the KOH aqueous solution can be 0.2~2mol / L; in a specific embodiment of the present invention, the concentration of the KOH aqueous solution is 0.2mol / L, 0.5mol / L, 1mol / L, 1.5mol / L or 2mol / L. In the present invention, the electrochemical oxidation can be carried out under oxygen saturation conditions. The conditions of the electrochemical oxidation of the present invention include: the oxidation time can be 50~200s, and the load voltage can be 1.2~2.5V; in a specific embodiment of the present invention, the oxidation time of the electrochemical oxidation is 80s, 100s or 150s; the load voltage is 1.2V, 1.5V or 2V. After the electrochemical oxidation is completed, the present invention sequentially washes and dries the obtained material. The washing of the present invention includes sequentially alcohol washing and water washing; the reagent used for the alcohol washing can be anhydrous ethanol. The drying of the present invention can be carried out in a N2 atmosphere.

[0033] After obtaining the precursor, the present invention places the precursor in a precursor solution for hydrothermal reaction to form a catalytic activity enhancement layer on the surface of the precursor to obtain the transition metal composite material. In the present invention, the precursor solution is an alkaline aqueous solution containing transition metal ions. The transition metal ions of the present invention include a first transition metal ion and a second transition metal ion; the first transition metal ion includes Co ions, Cu ions, Ni ions, Zn ions, Mn ions or Ti ions; the second transition metal ion is Fe ion; the composition of the catalytic activity enhancement layer is a layered double metal hydroxide with a molecular formula of M1M2-LDH, where M1 includes Co, Cu, Ni, Zn, Mn or Ti, and M2 is Fe. In the present invention, the precursor solution may include a first transition metal salt, a second transition metal salt, ammonium fluoride, urea and water; the first transition metal salt may include a Co salt, a Cu salt, a Ni salt, a Zn salt, a Mn salt or a Ti salt, and the second transition metal salt is an Fe salt; the concentration of the first transition metal ion in the precursor solution may be 0.004-0.05 mmol / L, and the concentration of the second transition metal ion may be 0.004-0.05 mmol / L. In a specific embodiment of the present invention, the precursor solution is composed of a Co salt, a Fe salt, ammonium fluoride, urea and water. In the present invention, the Co salt may include cobalt nitrate, cobalt chloride or cobalt sulfate; the cobalt nitrate may be hexahydrated cobalt nitrate (Co(NO3)2·6H2O). The Fe salt of the present invention may include ferric nitrate, ferric chloride or ferric sulfate; the ferric nitrate may be nonahydrated ferric nitrate (Fe(NO3)3·9H2O). In a specific embodiment of the present invention, the first transition metal salt is Co(NO3)2·6H2O, and the second transition metal is Fe(NO3)3·9H2O, wherein the molar ratio of Co ions to Fe ions is 3:7, 1:1 or 7:3. In the precursor solution of the present invention, the dosage ratio of the Co salt to water can be (0.2~1)mmol:(20~50)mL. In the present invention, the molar ratio of the Co salt, the Fe salt, the ammonium fluoride and the urea in the precursor solution can be 0.2~1:0.2~1:2~8:5~10. In a specific embodiment of the present invention, the precursor solution is composed of Co(NO3)2·6H2O, Fe(NO3)3·9H2O, ammonium fluoride, urea and water; wherein the molar ratio of Co(NO3)2·6H2O, Fe(NO3)3·9H2O, ammonium fluoride and urea is 0.5:0.5:3.5:8.5, 0.3:0.7:3.5:8.5 or 0.7:0.3:3.5:8.5, and the volume of water is 30mL. The concentration of Co ions in the precursor solution of the present invention can be 0.004~0.05mmol / L, and the concentration of Fe ions can be 0.004~0.05mmol / L.In an embodiment of the present invention, Co(NO3)2·6H2O, Fe(NO3)3·9H2O, ammonium fluoride, urea and water are mixed in proportion to obtain a precursor solution. In the present invention, the mixing can be carried out under stirring, and the stirring can be magnetic stirring; the stirring time can be 15 minutes. In the present invention, the precursor can be placed horizontally in the precursor solution so that the precursor is completely immersed in the precursor solution. The temperature of the hydrothermal reaction of the present invention can be 110~165℃, and the insulation time can be 6~18h. In a specific embodiment of the present invention, the temperature of the hydrothermal reaction is 110℃, 130℃, 150℃ or 165℃; the insulation time is 6h, 10h, 14h or 18h. In a specific embodiment of the present invention, the hydrothermal reaction is carried out in a stainless steel hydrothermal reactor with a 100mL polytetrafluoroethylene substrate. After the hydrothermal reaction of the present invention is completed, the pH value of the obtained liquid can be 12-14; in a specific embodiment of the present invention, the pH value of the obtained liquid after the hydrothermal reaction is completed is 12, 13 or 14. After the hydrothermal reaction is completed, the present invention can cool the obtained liquid to room temperature, perform solid-liquid separation, collect solid materials and wash and dry the solid materials in sequence. The solid-liquid separation of the present invention can be filtration; the washing can include alcohol washing and water washing in sequence; the reagent used for the alcohol washing can be anhydrous ethanol. In the present invention, the purpose of the washing is to remove precipitation and impurities on the surface of the solid material. The drying of the present invention can be vacuum drying; the temperature of the vacuum drying can be 50-70°C, and the time can be 6-12h; in an embodiment of the present invention, the temperature of the vacuum drying is 50°C, 60°C or 70°C; the time is 6h, 8h, 10h or 12h.

[0034] In the present invention, the transition metal composite material comprises a plurality of lamellar structure particles; each of the lamellar structure particles grows on the surface of the foamed transition metal, and each of the lamellar structure particles may have a diameter of 10-30 nm and a thickness of 500-1000 nm.

[0035] The present invention combines different functional layers to obtain the transition metal composite material, wherein the preparation process of each functional layer is independent of each other and does not interfere with each other. The self-supporting transition metal composite material formed by this step-by-step functionalization method has a large void, which increases the specific surface area; when the transition metal composite material is used as an OER catalyst in OER, the pores can provide an entry path for the electrolyte to ensure the formation of a three-phase interface of the OER catalyst, reactants and electrolyte; at the same time, the surface active sites of the OER catalyst are increased, the functionalized structure of the OER catalyst is optimized, the utilization rate of the catalyst active sites is increased, and the amount of transition metal used is reduced. In addition, the preparation process of the transition metal composite material of the present invention is carbon-free and adhesive-free, avoiding the problem of catalytic layer shedding caused by adhesive aging and carbon corrosion, and the preparation process is simple and the preparation cost is low.

[0036] The present invention also provides the transition metal composite material described in the above technical solution or the use of the transition metal composite material described in the above technical solution as an OER catalyst or in a sodium ion battery.

[0037] The transition metal composite material of the present invention has good structural stability, OER activity and durability, and has a simple preparation method, low cost and good application prospect.

[0038] The present invention also provides a sodium ion battery, comprising a positive electrode, a negative electrode, an electrolyte and an acidic substance absorbing diaphragm; the acidic substance absorbing diaphragm comprises a polypropylene base film and an acidic substance adsorption slurry layer coated on the surface of the polypropylene base film; the coating method comprises an extrusion coating method, a gravure coating method or a dip coating method; the raw material for preparing the acidic substance adsorption slurry layer comprises the transition metal composite material described in the above technical solution or the transition metal composite material described in the above technical solution.

[0039] In the present invention, the thickness of the polypropylene base film may be 6-15 μm, and the thickness of the acidic substance adsorption slurry layer may be 1-5 μm. In a specific embodiment of the present invention, the thickness of the polypropylene base film is 9 μm, and the thickness of the acidic substance adsorption slurry layer may be 3 μm. The acidic substance absorption membrane of the present invention includes an acidic substance adsorption slurry layer, and the raw materials for preparing the acidic substance adsorption slurry layer include transition metal composite materials; the mass proportion of the transition metal composite material in the acidic substance absorption membrane may be 5%-15%. In a specific embodiment of the present invention, the mass proportion of the transition metal composite material in the acidic substance absorption membrane is 5%, 10% or 15%. The raw materials for preparing the acidic substance adsorption slurry layer of the present invention may include a binder, a conductive agent, a safener, boehmite, an organic solvent and a transition metal composite material; the binder may be polyvinylidene fluoride (PVDF); the conductive agent may be conductive carbon black (SP); and the organic solvent may be N-methylpyrrolidone (NMP). In the present invention, the mass ratio of the binder, the conductive agent, the safener, the boehmite and the transition metal composite material can be 50~75:5~20:2~8:2~8:5~15. In a specific embodiment of the present invention, the mass ratio of the binder, the conductive agent, the safener, the boehmite and the transition metal composite material is 65:15:5:5:10. The preparation method of the acidic substance absorbing diaphragm of the present invention comprises the following steps: mixing the binder, the conductive agent, the safener and the transition metal composite material under stirring to obtain a mixture; mixing an organic solvent with the mixture to obtain an acidic substance absorbing slurry; coating the acidic substance absorbing slurry on the side of the polypropylene base film close to the negative electrode to prepare an acidic substance adsorption slurry layer on the surface of the polypropylene base film to obtain a diaphragm; drying the diaphragm to obtain an acidic substance absorbing diaphragm. In the present invention, the coating method comprises an extrusion coating method, a gravure coating method or a dip coating method. In the present invention, the solid content of the acidic substance absorption slurry can be 50-70%; in a specific embodiment of the present invention, the solid content of the acidic substance absorption slurry is 58%. In the present invention, the coating process can be a gravure coating process; the conditions of the gravure coating process include: the speed ratio can be 100-130%; the host speed can be 3-10m / min; the wrap angle can be 5-15°; the scraper pressure can be 1-5kg. In a specific embodiment of the present invention, the conditions of the gravure coating process are as follows: the speed ratio is 120%; the host speed is 5m / min; the wrap angle is 10°; the scraper pressure is 3kg. In the present invention, the drying temperature can be 70-90°C, and the time can be 2-4h; in a specific embodiment of the present invention, the drying temperature is 70°C, 80°C or 90°C; the time is 2h, 3h or 4h.

[0040] In the present invention, the constituent material of the positive electrode of the sodium ion battery may include composite sodium iron phosphate (NFPP). In the present invention, the raw materials for preparing the positive electrode of the sodium ion battery may include composite sodium iron phosphate, solvent, binder, dispersant and conductive agent; the solvent may be N-methylpyrrolidone (NMP); the binder may be polyvinylidene fluoride (PVDF); the dispersant may be polyvinyl pyrrolidone (PVP); the conductive agent may be conductive carbon black (SP). In the present invention, the mass ratio of the composite sodium iron phosphate (NFPP), conductive agent (SP), binder (PVDF) and dispersant (PVP) may be 92~96:1~5:1~3:0.3~1.

[0041] In a specific embodiment of the present invention, the constituent materials of the positive electrode of the sodium ion battery are composed of composite sodium iron phosphate, N-methylpyrrolidone, polyvinylidene fluoride, polyvinyl pyrrolidone and conductive carbon black; the mass ratio of the polyanionic composite sodium iron phosphate, N-methylpyrrolidone, polyvinylidene fluoride, polyvinyl pyrrolidone and conductive carbon black is 63:22:3:2:5. The present invention can mix the raw materials for preparing the positive electrode of the sodium ion battery, and obtain the positive electrode slurry after homogenization; the positive electrode slurry is coated on aluminum foil, and the drying, coating, drying, rolling and slitting processes are carried out in sequence to obtain the positive electrode. In the present invention, the homogenization time can be 4~8h; in a specific embodiment of the present invention, the homogenization time is 6h. In the present invention, the solid content of the positive electrode slurry can be 55~65%; the fineness can be 30~45μm; the viscosity can be 5000~7000MPa·S. In a specific embodiment of the present invention, the positive electrode slurry has a solid content of 62%, a fineness of 40 μm, and a viscosity of 6500 MPa·S. In the present invention, the drying temperature may be 70-90°C, and the drying time may be 2-4 hours; in a specific embodiment of the present invention, the drying temperature is 70°C, 80°C, or 90°C; and the drying time is 2 hours, 3 hours, or 4 hours.

[0042] In the present invention, the constituent material of the negative electrode of the sodium ion battery may include hard carbon. In the present invention, the raw materials for preparing the sodium ion battery may include hard carbon, conductive carbon black, styrene butadiene rubber (SBR), carboxymethyl cellulose (CMC) and water. In the present invention, the mass ratio of the hard carbon, conductive carbon black, styrene butadiene rubber and carboxymethyl cellulose may be 90~95:2~5:1~2:1~2; in a specific embodiment of the present invention, the mass ratio of the hard carbon, conductive carbon black, styrene butadiene rubber and carboxymethyl cellulose is 93:4:1.5:1.5. In the present invention, the raw materials for preparing the negative electrode of the sodium ion battery may be mixed, and the negative electrode slurry may be obtained after homogenization; the negative electrode slurry may be coated on aluminum foil and sequentially dried, coated, dried, rolled and cut to obtain the negative electrode. In the present invention, the homogenization time may be 3~7h; in a specific embodiment of the present invention, the homogenization time is 5h. In the present invention, the solid content of the negative electrode slurry can be 30-50%; the pH value can be 7-9.5; the fineness can be 20-30 μm; and the viscosity can be 3000-5000 MPa·S. In a specific embodiment of the present invention, the solid content of the positive electrode slurry is 40%, the pH value is 8.6, the fineness is 22 μm, and the viscosity is 4000 MPa·S. In the present invention, the drying temperature can be 70-90°C, and the time can be 2-4h; in a specific embodiment of the present invention, the drying temperature is 70°C, 80°C or 90°C; and the time is 2h, 3h or 4h.

[0043] In the present invention, the electrolyte of the sodium ion battery may be a liquid containing sodium hexafluorophosphate. In the present invention, the raw materials for preparing the electrolyte of the sodium ion battery may include sodium hexafluorophosphate, ethyl cellulose (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC); the mass ratio of the sodium hexafluorophosphate, ethyl cellulose, dimethyl carbonate and ethyl methyl carbonate may be 90~96:1~4:1.5~3:1.5~3. In a specific embodiment of the present invention, the mass ratio of the sodium hexafluorophosphate, ethyl cellulose, dimethyl carbonate and ethyl methyl carbonate is 94:2:2:2. The present invention mixes the raw materials for preparing the electrolyte to obtain the electrolyte of the sodium ion battery.

[0044] After obtaining the positive electrode, the negative electrode, the electrolyte and the acidic substance absorbing membrane, the present invention assembles the positive electrode, the negative electrode, the electrolyte and the acidic substance absorbing membrane to obtain a bare cell; the bare cell is sequentially packaged, injected, formed and divided into different volumes to obtain a sodium ion battery. In the present invention, the capacity of the sodium ion battery can be 10 to 200 Ah; in a specific embodiment of the present invention, the capacity of the sodium ion battery is 14 Ah.

[0045] The transition metal composite material in the sodium ion battery of the present invention can effectively absorb acidic substances such as HF and CO2 generated by the electrolyte, and effectively prevent the acidic substances from having side reactions with the positive and negative electrode materials and the electrolyte inside the sodium ion battery, thereby effectively improving the capacity retention rate and cycle stability of the sodium ion battery.

[0046] In the present invention, there are adsorption sites for acidic substances such as HF and CO2 in the anion layer of the transition metal composite material, including hydroxyl sites, vacancies and edge sites. The presence of these sites can promote the adsorption of acidic substances such as HF and CO2 and improve their adsorption capacity. Moreover, the layered double hydroxide (LDH) in the transition metal composite material can be used as an acid absorbent in the sodium ion battery to absorb the acidic substances ionized by the sodium supplement, and can also interact with the molecules of acidic substances such as HF and CO2 through electrostatic interactions, hydrogen bonds and van der Waals forces, thereby increasing the residence time of acidic substances such as HF and CO2 in the material, absorbing the acidic substances such as HF produced by the side reaction of the electrolyte, optimizing the electrolyte composition, and thus further improving the cycle performance of the sodium ion battery. Furthermore, transition metal oxides react chemically with acidic molecules such as HF and CO2 through the chemically active sites on their surfaces (such as the Fe-O bonds in FeO) to form stable chemical bonds. For example, on the FeO surface, HF and CO2 molecules are adsorbed at specific sites (such as oxygen top sites, bridge sites and vacancies) to form specific chemical structures. At the same time, transition metal oxides can also physically adsorb HF and CO2 molecules through the physical adsorption sites on their surfaces (such as electron-deficient oxygen vacancies). Chemical bonds are not formed, but the adsorption of acidic substances is achieved through electron transfer and intermolecular interactions.

[0047] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] The foamed iron used in the embodiment has a porosity of 98% and a specific surface area of ​​30 cm² / cm³, and is a commercially available product.

[0049] Example 1 (1) Cut the 1 mm thick foam iron into small cubes (2 cm long × 2 cm wide), place the foam iron in 3% mass fraction dilute hydrochloric acid, and ultrasonically treat it at 60 kHz for 15 min. Then place the foam iron in acetone and ultrasonically treat it at 60 kHz for 15 min. After that, wash the foam iron with anhydrous ethanol and deionized water in turn, and then dry it naturally in a N2 atmosphere for later use.

[0050] (2) The foamed iron treated in step (1) is placed in a KOH aqueous solution with a concentration of 1 mol / L, and electrochemically oxidized under oxygen saturation conditions, wherein the conditions include: a load potential of 1.5 V, and an oxidation time of 80 s. After completion, the obtained material is washed with anhydrous ethanol and deionized water in turn, and then naturally dried in a N2 atmosphere to prepare a precursor (porous foamed Fe2O3 / Fe).

[0051] (3) 0.5mmol Co(NO3)2·6H2O, 0.5mmol Fe(NO3)3·9H2O, 3.5mmol NH4F and 8.5mmol urea were mixed with 30mL deionized water and magnetically stirred for 15min to make them evenly dispersed to obtain a precursor solution. The precursor prepared in step (2) was placed horizontally in the precursor solution so that the precursor was completely immersed in the precursor solution. The obtained material solution was transferred to a stainless steel hydrothermal reactor with a 100mL polytetrafluoroethylene substrate for hydrothermal reaction. The temperature of the hydrothermal reaction was 130°C and the insulation time was 10h. After the hydrothermal reaction was completed, the reactor was naturally cooled to room temperature, filtered, and solid materials and liquid materials were collected. The pH value of the liquid material was 13; the solid material was washed with anhydrous ethanol and deionized water in turn, and the washed material was placed in a vacuum drying oven and dried at 60°C for 5h to obtain a transition metal composite material (referred to as CoFe-LDH / Fe2O3 / Fe composite material).

[0052] Test Example 1 The CoFe-LDH / Fe2O3 / Fe composite material obtained in Example 1 was subjected to XRD test analysis. The test results are as follows: Figure 1 shown.

[0053] Depend on Figure 1 It can be seen that in the XRD pattern of CoFe-LDH / Fe2O3 / Fe composite material, the diffraction peaks at 11.5°, 22.7°, 33.4°, 38.7°, 45.9° and 59.8° correspond to the (003), (006), (012), (015), (018) and (110) crystal planes of CoFe-LDH, respectively; the diffraction peaks at 24.1°, 33.1°, 35.6°, 49.2° and 54.2° correspond to the (012), (104), (110), (024) and (116) crystal planes of Fe2O3, respectively. The above results indicate the successful synthesis of CoFe-LDH / Fe2O3 / Fe composite material.

[0054] Test Example 2 The microstructure of the CoFe-LDH / Fe2O3 / Fe composite material obtained in Example 1 was observed by scanning electron microscopy (SEM). Figure 2 As shown, Figure 2 (a) is the SEM image of the CoFe-LDH / Fe2O3 / Fe composite material under a low-magnification microscope, and (b) is the SEM image of the CoFe-LDH / Fe2O3 / Fe composite material under a high-magnification microscope.

[0055] Depend on Figure 2 It can be seen that the CoFe-LDH / Fe2O3 / Fe composite material grows uniformly on the surface of the foam transition metal in a lamellar structure with a diameter of 10~30nm and a thickness of 500~1000nm. The lamellar porous structure allows the CoFe-LDH / Fe2O3 / Fe composite material to expose more active sites during the OER reaction and is conducive to the release of reaction intermediates and gases. Moreover, as a good electrical conductor, the foam transition metal can effectively promote the electron transport of the CoFe-LDH / Fe2O3 / Fe composite material, reduce its electrochemical impedance and effectively avoid the agglomeration of CoFe-LDH / Fe2O3.

[0056] Example 2 The transition metal composite material was prepared in the manner and conditions of Example 1, except that the amount of Co(NO3)2·6H2O in the precursor solution used in step (3) was adjusted to 0.3 mmol, and the amount of Fe(NO3)3·9H2O was adjusted to 0.7 mmol, and the other conditions remained unchanged. The transition metal composite material prepared in Example 2 was recorded as Co3Fe7-LDH / Fe2O3 / Fe composite material.

[0057] Example 3 The transition metal composite material was prepared in the manner and conditions of Example 1, except that the amount of Co(NO3)2·6H2O in the precursor solution used in step (3) was adjusted to 0.7 mmol, and the amount of Fe(NO3)3·9H2O was adjusted to 0.3 mmol, and the other conditions remained unchanged. The transition metal composite material prepared in Example 3 was recorded as Co7Fe3-LDH / Fe2O3 / Fe composite material.

[0058] Comparative Example 1 A ruthenium-iron-based composite material (RuO2 / Fe2O3 / Fe composite material) was prepared in the manner and conditions of Example 1, except that the composition of the precursor solution used in step (3) was adjusted to 1 mmol RuO2, 3.5 mmol NH4F, 8.5 mmol urea and 30 mL deionized water, and other conditions remained unchanged.

[0059] Comparative Example 2 Cut the 1mm thick transition metal foam into small cubes (2cm long × 2cm wide), place the transition metal foam in 3% mass fraction dilute hydrochloric acid, and ultrasonically treat it at 60kHz for 15min. Then place the transition metal foam in acetone and ultrasonically treat it at 60kHz for 15min. After that, wash the transition metal foam with anhydrous ethanol and deionized water in turn, and then dry it naturally in N2 atmosphere to obtain a transition metal foam sample.

[0060] Test Example 3 OER activity test In the electrochemical reaction process, overpotential is an important parameter used to describe the OER activity of the catalyst. The overpotential of the catalyst is generally calculated using the LSV curve. Usually, the potential when a certain current density value is reached is defined as the overpotential (η), η=E RHE -1.23 V. The lower the overpotential of the catalyst, the lower the energy barrier it needs to overcome in the OER process and the stronger its OER kinetics.

[0061] The OER activity test was performed on the CoFe-LDH / Fe2O3 / Fe composite material obtained in Example 1, the Co3Fe7-LDH / Fe2O3 / Fe composite material obtained in Example 2, the Co7Fe3-LDH / Fe2O3 / Fe composite material obtained in Example 3, the RuO2 / Fe2O3 / Fe composite material obtained in Comparative Example 1, and the foam transition metal sample obtained in Comparative Example 2. The specific test conditions are as follows: a KOH aqueous solution with a concentration of 1 mol / L, a potential window of 0-0.8 V Hg / HgO, and a scan rate of 0.01 V / s. The test results are shown in Figure 2. Figure 3 shown.

[0062] Depend on Figure 3 It can be seen that the overpotential of the CoFe-LDH / Fe2O3 / Fe composite material obtained in Example 1 is 236.6 mV, the overpotential of the Co3Fe7-LDH / Fe2O3 / Fe composite material obtained in Example 2 is 262.4 mV, and the overpotential of the Co7Fe3-LDH / Fe2O3 / Fe composite material obtained in Example 3 is 247.2 mV; this shows that when the molar ratio of Co ions to Fe ions is 1:1, CoFe-LDH has the best OER catalytic activity, which can be attributed to the fact that CoFe-LDH has the best electronic structure at this time, which can effectively reduce the OER reaction energy barrier.

[0063] Moreover, by Figure 3It can be seen that the overpotential of the CoFe-LDH / Fe2O3 / Fe composite material obtained in Example 1 is 46.2 mV lower than the overpotential of the RuO2 / Fe2O3 / Fe composite material obtained in Comparative Example 1, and 92.6 mV lower than the overpotential of the foam transition metal sample obtained in Comparative Example 2. The results show that the CoFe-LDH / Fe2O3 / Fe composite material has better OER reaction kinetics, which can be attributed to the synergistic effect of CoFe-LDH and Fe2O3 that effectively reduces the energy barrier of the OER reaction and improves the OER activity of the CoFe-LDH / Fe2O3 / Fe composite material.

[0064] Test Example 4 Electrochemical Impedance Test The electrochemical impedance spectroscopy (EIS) of a catalyst is an important indicator for evaluating its charge transfer ability in OER. The CoFe-LDH / Fe2O3 / Fe composite material obtained in Example 1, the Co3Fe7-LDH / Fe2O3 / Fe composite material obtained in Example 2, the Co7Fe3-LDH / Fe2O3 / Fe composite material obtained in Example 3, the RuO2 / Fe2O3 / Fe composite material obtained in Comparative Example 1, and the foam transition metal sample obtained in Comparative Example 2 were subjected to electrochemical impedance spectroscopy. The results are shown in FIG. Figure 4 shown.

[0065] Depend on Figure 4 It can be seen that under the same test conditions, the electrochemical impedance of the CoFe-LDH / Fe2O3 / Fe composite material obtained in Example 1 is Rct=6.3Ω, the electrochemical impedance of the Co3Fe7-LDH / Fe2O3 / Fe composite material obtained in Example 2 is Rct=7.6Ω, and the electrochemical impedance of the Co7Fe3-LDH / Fe2O3 / Fe composite material obtained in Example 3 is Rct=6.8Ω, which indicates that when the molar ratio of Co ions to Fe ions is 1:1, CoFe-LDH has the best electron transport capacity and can effectively promote the transfer of electrons and the conversion process of intermediate products in the OER reaction.

[0066] At the same time, the electrochemical impedance of the RuO2 / Fe2O3 / Fe composite material obtained in Comparative Example 1 is Rct=8.5Ω, and the electrochemical impedance of the foam transition metal sample obtained in Comparative Example 2 is Rct=11.2Ω; that is, the electrochemical impedance of the CoFe-LDH / Fe2O3 / Fe composite material obtained in Example 1 is smaller than that of the RuO2 / Fe2O3 / Fe composite material and the foam transition metal obtained in Comparative Example 1, which indicates that the CoFe-LDH / Fe2O3 / Fe composite material can reduce the electron transmission resistance in the OER process and improve the electron transfer efficiency.

[0067] Test Example 5 OER durability test At a constant potential of 0.8 V vs. Hg / HgO, the CoFe-LDH / Fe2O3 / Fe composite material obtained in Example 1, the Co3Fe7-LDH / Fe2O3 / Fe composite material obtained in Example 2, the Co7Fe3-LDH / Fe2O3 / Fe composite material obtained in Example 3, the RuO2 / Fe2O3 / Fe composite material obtained in Comparative Example 1, and the foam transition metal sample obtained in Comparative Example 2 were subjected to an IT durability test for up to 30 hours. The test results are shown in FIG. Figure 5 shown.

[0068] Depend on Figure 5 It can be seen that after 30 hours of continuous operation, the CoFe-LDH / Fe2O3 / Fe composite material obtained in Example 1 has the highest current density of 91.7 mA / cm 2 The current density of the Co3Fe7-LDH / Fe2O3 / Fe composite material obtained in Example 2 is 83.9 mA / cm 2 The current density of the Co7Fe3-LDH / Fe2O3 / Fe composite material obtained in Example 3 is 88.4 mA / cm 2 , which indicates that when the molar ratio of Co ions to Fe ions is 1:1, CoFe-LDH has the optimal electronic structure, resulting in excellent long-cycle durability.

[0069] At the same time, the current density of the RuO2 / Fe2O3 / Fe composite material obtained in Comparative Example 1 was only 67.6 mA / cm 2 The current density of the transition metal foam sample obtained in Comparative Example 2 is only 40.2 mA / cm 2 , which are far lower than the current density of the CoFe-LDH / Fe2O3 / Fe composite material obtained in Example 1. This can be attributed to the continuous surface reconstruction of the CoFe-LDH / Fe2O3 / Fe composite material due to its own adaptive effect during continuous operation, which optimizes the electronic structure of the surface of the CoFe-LDH / Fe2O3 / Fe composite material. In addition, as the IT process continues, the active sites in the layered structure inside the CoFe-LDH / Fe2O3 / Fe composite material will be continuously exposed, thereby promoting the improvement of its OER durability.

[0070] Example 4 (1) The CoFe-LDH / Fe2O3 / Fe composite material prepared in Example 1 was placed in a beaker, and the beaker was placed in an ultrasonic instrument. Ultrasonic treatment was performed for 20 minutes at an ultrasonic frequency of 50 KHz to peel the CoFe-LDH / Fe2O3 composite material from the surface of the foamed iron (substrate) to obtain a CoFe-LDH / Fe2O3 composite material. The CoFe-LDH / Fe2O3 composite material was placed in a ball mill and fully ground to obtain a CoFe-LDH / Fe2O3 composite material powder with a particle size of 0.5-10 μm.

[0071] (2) PVDF, SP, safety agent, boehmite and CoFe-LDH / Fe2O3 composite material powders were weighed in a mass ratio of 65:15:5:5:10, and the weighed materials were stirred and mixed to prepare a mixture. A solvent (NMP) was added to the above mixture to obtain an acidic substance absorption slurry with a solid content of 58%. The acidic substance absorption slurry was coated on a side of a polypropylene base film with a thickness of 9 μm close to the negative electrode by a gravure coating process to prepare an acidic substance adsorption slurry layer on the surface of the polypropylene base film to obtain a diaphragm, wherein the coating parameters of the gravure coating process are as follows: speed ratio is 120%; main machine speed is 5 m / min; wrap angle is 10°; scraper pressure is 3 kg. After coating, the obtained diaphragm was dried at 80°C for 5 hours to prepare an acidic substance adsorption slurry layer on the surface of the polypropylene base film, thereby obtaining an acidic substance absorption diaphragm containing a CoFe-LDH / Fe2O3 composite material, wherein the thickness of the acidic substance adsorption slurry layer was 3 μm.

[0072] (3) Preparation of positive electrode sheets: Composite sodium iron phosphate (NFPP), conductive agent (SP), binder (PVDF) and dispersant (PVP) were weighed in a mass ratio of 95:3:1.5:0.5, and a solvent (NMP) was added and mixed for 6 hours to obtain a positive electrode slurry with a solid content of 62%, a fineness of 40 μm, and a viscosity of 6500 MPa·S. The slurry was coated on aluminum foil and dried at 80°C for 3 hours. The positive electrode sheets were then made by coating, drying, rolling and slitting.

[0073] (4) Preparation of negative electrode sheets: Hard carbon, conductive carbon black, SBR and CMC were mixed with deionized water in a mass ratio of 93:4:1.5:1.5 and stirred for 5 h to obtain a negative electrode slurry with a solid content of 40%, a pH value of 8.6, a fineness of 22 μm and a viscosity of 4000 MPa·S. The slurry was coated on aluminum foil and dried at 80°C for 3 h. The slurry was then coated, dried, rolled and cut to produce negative electrode sheets.

[0074] (5) Preparation of electrolyte: Sodium hexafluorophosphate, EC, DMC and EMC were mixed in a mass ratio of 94:2:2:2 to prepare an electrolyte.

[0075] (6) Battery assembly and activation: The positive electrode sheet, the negative electrode sheet, the electrolyte and the acidic substance absorption diaphragm containing the CoFe-LDH / Fe2O3 composite material are assembled to obtain a bare cell; the bare cell is packaged, injected, formed and divided into different volumes in sequence to prepare a sodium ion battery with a capacity of 14Ah.

[0076] Comparative Example 3 A sodium ion battery was prepared in the manner and conditions of Example 4, except that the CoFe-LDH / Fe2O3 composite material powder was not added during the preparation of the acidic substance absorption membrane in step (2).

[0077] Comparative Example 4 A sodium ion battery was prepared in the manner and conditions of Example 4, except that the mass ratio of PVDF, SP, safener, boehmite and CoFe-LDH / Fe2O3 composite material powder in the acidic substance absorption membrane in step (2) was adjusted to 65:15:5:5:2.

[0078] Comparative Example 5 A sodium ion battery was prepared in the manner and conditions of Example 4, except that in step (2), the mass ratio of PVDF, SP, safener, boehmite and CoFe-LDH / Fe2O3 composite material powder in the acidic substance absorption membrane was adjusted to 65:15:5:5:5.

[0079] Comparative Example 6 A sodium ion battery was prepared in the manner and under the conditions of Example 4, except that in step (2), the mass ratio of PVDF, SP, safener, boehmite and CoFe-LDH / Fe2O3 composite material powder in the acidic substance absorption diaphragm was adjusted to 65:15:5:5:15; Test Example 6: Capacity retention test of sodium ion battery after 500 cycles At 25±2°C, 3 cells were taken from each of the sodium ion batteries obtained in Example 4 and Comparative Examples 3 to 6 to test the capacity retention rate after 500 cycles. The test method is as follows: First, the sodium ion battery was left to stand for 25 minutes, then charged to 3.5V at 0.5C constant current and constant voltage, left to stand for 25 minutes, and then charged to 0.05C at constant voltage; after standing for 25 minutes, it was discharged to 1.5V at 0.5C constant current and left to stand for 25 minutes. The above process was continued, and the average value of the capacity retention rate of each group of sodium ion batteries after 500 cycles was recorded. The results are shown in Table 1.

[0080] Table 1 Capacity retention test results of different sodium ion batteries after 500 cycles

[0081] The results show that the sample without adding CoFe-LDH / Fe2O3 composite material to the acidic substance absorption membrane (Comparative Example 3) has the lowest capacity retention rate after 500 cycles, which is 93.34%; when the mass ratio of binder PVDF, conductive agent SP, safety agent, boehmite and CoFe-LDH / Fe2O3 composite material powder in the acidic substance absorption membrane is 65:15:5:5:10 (Example 4), the capacity retention rate of the sodium ion battery after 500 cycles is the best, which is 96.52%. This can be attributed to the fact that the content of the acidic substance in the battery cell and the CoFe-LDH / Fe2O3 composite material is most matched at this time, and the CoFe-LDH / Fe2O3 composite material in the acidic substance absorption membrane can fully absorb the acidic substances generated during the battery cycle, and will not affect the safety performance and energy density of the sodium ion battery.

[0082] In summary, adding an appropriate amount of CoFe-LDH / Fe2O3 composite material to sodium ion batteries can effectively improve the capacity retention and cycle stability of the battery.

[0083] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A transition metal composite material, characterized in that: It comprises a conductive substrate, an adsorption layer coated on the surface of the conductive substrate, and a catalytic activity enhancement layer coated on the surface of the adsorption layer; The conductive substrate is a foam transition metal; the foam transition metal includes foam iron, foam cobalt, foam copper, foam nickel, foam zinc, foam manganese or foam titanium; The adsorption layer is composed of oxides of transition metals in the conductive substrate; The catalytic activity enhancement layer is composed of layered double metal hydroxides with a molecular formula of M1M2-LDH, where M1 includes Co, Cu, Ni, Zn, Mn or Ti, and M2 is Fe.

2. The transition metal composite material according to claim 1, characterized in that The foam transition metal is a three-dimensional network structure; the thickness of the conductive substrate is 0.3-2 mm.

3. The transition metal composite material according to claim 1, characterized in that: The transition metal composite material comprises a plurality of flaky structure particles; each of the flaky structure particles has a diameter of 10-30 nm and a thickness of 500-1000 nm.

4. The method for preparing the transition metal composite material according to any one of claims 1 to 3, comprising the following steps: Electrochemically oxidizing the surface of a transition metal foam to obtain a precursor; the precursor comprises a conductive substrate and an adsorption layer coated on the surface of the conductive substrate; the conductive substrate is a transition metal foam, and the transition metal foam comprises iron foam, cobalt foam, copper foam, nickel foam, zinc foam, manganese foam or titanium foam, and the adsorption layer is composed of oxides of the transition metal in the conductive substrate; The precursor is placed in a precursor liquid for hydrothermal reaction to form a catalytic activity enhancement layer on the surface of the precursor to obtain the transition metal composite material; the precursor liquid is an alkaline aqueous solution containing transition metal ions; the transition metal ions include first transition metal ions and second transition metal ions; the first transition metal ions include Co ions, Cu ions, Ni ions, Zn ions, Mn ions or Ti ions; the second transition metal ions are Fe ions; the composition of the catalytic activity enhancement layer is a layered double metal hydroxide with a molecular formula of M1M2-LDH, where M1 includes Co, Cu, Ni, Zn, Mn or Ti, and M2 is Fe.

5. The preparation method according to claim 4, characterized in that: The electrochemical oxidation is carried out in an electrolyte; the conditions of the electrochemical oxidation include: an oxidation time of 50 to 200 seconds and a load voltage of 1.2 to 2.5V.

6. The preparation method according to claim 5, characterized in that: The electrolyte includes a KOH aqueous solution, and the concentration of the KOH aqueous solution is 0.2-2 mol / L.

7. The preparation method according to claim 4, characterized in that: The precursor solution includes a first transition metal salt, a second transition metal salt, ammonium fluoride, urea and water; the first transition metal salt includes Co salt, Cu salt, Ni salt, Zn salt, Mn salt or Ti salt, and the second transition metal salt is Fe salt; the concentration of the first transition metal ion in the precursor solution is 0.004~0.05mmol / L, and the concentration of the second transition metal ion is 0.004~0.05mmol / L; the temperature of the hydrothermal reaction is 110~165℃, and the insulation time is 6~18h.

8. Use of the transition metal composite material according to any one of claims 1 to 3 or the transition metal composite material obtained by the preparation method according to any one of claims 4 to 7 as an OER catalyst or in a sodium ion battery.

9. A sodium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode, an electrolyte and an acidic substance absorbing diaphragm; the acidic substance absorbing diaphragm comprises a polypropylene base film and an acidic substance adsorption slurry layer coated on the surface of the polypropylene base film; the coating method comprises an extrusion coating method, a gravure coating method or a dip coating method; the raw material for preparing the acidic substance adsorption slurry layer comprises the transition metal composite material according to any one of claims 1 to 3 or the transition metal composite material obtained by the preparation method according to any one of claims 4 to 7.

10. The sodium ion battery according to claim 9, characterized in that: The mass proportion of the transition metal composite material in the acidic substance absorption diaphragm is 5% to 15%; the electrolyte is a liquid containing sodium hexafluorophosphate; the component material of the positive electrode includes composite sodium iron phosphate; and the component material of the negative electrode includes hard carbon.

Citation Information

Patent Citations

  • Method for preparing layered double hydroxide (LDH) closing film layer on surface of magnesium alloy

    CN106086992A

  • Nano-porous Ni-Fe double-metal layer laminated hydroxide electric catalytic material for oxygen evolution and preparation method and application of electric catalytic material

    CN107670667A

  • Fuel cell electrode and preparation method and application thereof

    CN114759197A

  • Nanofiber diaphragm material for sodium ion lithium battery and preparation method of nanofiber diaphragm material

    CN115000628A

  • Electrode material with high-performance oxygen evolution catalytic activity and preparation method thereof

    CN115094475A

Cited By

  • Dead-weight configuration oxygen evolution electrode, preparation method and application

    CN121472864A